2021
DOI: 10.1097/shk.0000000000001806
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Circulating Supar Levels with Inflammation, Fibrinolysis, and Outcome in Severe Burn Patients

Abstract: Background: Hyperfibrinolysis and pro/anti-inflammatory imbalance usually occur in the early stage of severe burns. Soluble urokinase-type plasminogen activator receptor (suPAR) is involved in fibrinolysis and inflammation. To date, the levels of circulating suPAR in non-survivors with severe burns remain unknown. This study aimed to investigate the early association between circulating suPAR levels and biomarkers of fibrinolysis, pro/anti-inflammatory, and prognosis. Methods: Sixty-four consecutive Chinese pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…No significant variables associated with severe burn injuries were identified in this study, although we observed increased clot formation at lower fibrinogen levels and higher DD levels. These findings are consistent with those of Lin et al’s study involving non-survival cases [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…No significant variables associated with severe burn injuries were identified in this study, although we observed increased clot formation at lower fibrinogen levels and higher DD levels. These findings are consistent with those of Lin et al’s study involving non-survival cases [ 17 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to several studies ( Laou et al, 2022 ; Lin et al, 2021 ), the suPAR level may change depend on the type of trauma, so that we did not include the patients with trauma in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients experiencing burns typically present complex resuscitation problems. Lin et al (10) from Fujian Medical University examine markers of fibrinolysis and pro- inflammatory and anti-inflammatory mediator balance in patients experiencing severe burns. A particular interest of this group is soluble urokinase-type plasminogen activator receptor (suPAR), a mediator of fibrinolysis and inflammation (10).…”
mentioning
confidence: 99%
“…Lin et al (10) from Fujian Medical University examine markers of fibrinolysis and pro- inflammatory and anti-inflammatory mediator balance in patients experiencing severe burns. A particular interest of this group is soluble urokinase-type plasminogen activator receptor (suPAR), a mediator of fibrinolysis and inflammation (10). Sixty-four patients with burns measuring at least 30% of the total body surface area were compared with 26 healthy volunteers.…”
mentioning
confidence: 99%